Viscous Oil Film Thermal Modeling of Hydrostatic Bearings With a Rectangular Microgroove Surface - Liu, Teng; Li, Chentao; Duan, Runze; Qu, Huiru; Chen, Faze; Zhou, Zhenlin; Zhang, Jianjun; Shi, Zhanqun (Frontiers in Energy Research, 2022)
The thermal effect of the viscous oil film of hydrostatic bearings is the key factor causing bearing errors, and the hydrostatic bearing working surface with microgroove structures can potentially inhibit the thermal effect and effectively ensure the bearing accuracy. In this study, a modeling method for oil film heat generation of hydrostatic bearings with a rectangular microgroove working surface is established, and the influence of microgroove design scales onto oil film heat generation is studied. First, the flowing field numerical simulation model of the hydrostatic bearing oil film is established and verified by the published analytical model. Based on the simulation method, oil film flowing behaviors of hydrostatic bearings with a rectangular microgroove working surface are studied. Then, by combining the analytical calculation of viscous heat generation of the hydrostatic oil film and its flowing field simulation, a modified oil film thermal modeling of hydrostatic bearings with the rectangular microgroove working surface is established. On this basis, the influence of the microgroove design scale onto oil film heat generation is studied. It can be concluded that with the appropriate scales of the rectangular microgroove, the working surface with microgrooves can reduce the average velocity of the viscous flow field of the hydrostatic bearing oil film and restrain its energy loss and heat generation.